Design and Development of Motorized Mashing Machine - Dr. Hanumanthe Gowda; Athul S; Deepak J; Bhavana K N; Hemanth D (International Journal of Scientific Research in Mechanical and Materials Engineering, 2025)
A big market exists for machineries in food processing. For each different type of cooking there exist a different variety of vessels and machines. For mashing one can find a variety of devices and machines. However, some are small and simple devices and other are big and bulky machines. The Mashing Machine, our mini project, is a medium scale machine that combines the cam and shaft mechanism and spring mechanism. A motor rotates the shaft, the shaft in turn rotates the cam. The masher is connected to the cam through linkages and spring mechanism. The frame is mostly made from mild steel. A power source, usually a battery is connected to motor. The motor rotates the cam. Linkages of suitable length connected to cam helps in converting the rotating motion to reciprocating motion. The reciprocating motion causes the masher to move up and down. The spring attached to masher helps in increasing the applied force on the masher. As the motor rotates it also rotates the rounded rod connected to motor shaft. Now the cam also rotates with the rod movement which is linked to the masher head with a spring. As the cam rotates the masher head is pulled up and released, between I is released it is released with added pressure from the spring driving it into the bowl.